The Impact of Influencer and Digital Marketing on Brand Awareness in MSMEs: A Case Study in the Creative Industry Sector in Medan City - Imran Karo Karo; Nahar Maganda Saragih; Hendro Sutomo Ginting (ProBisnis : Jurnal Manajemen, 2026)
This research is designed to assess the impact of influencer and social media marketing on the popularity of brands within MSMEs: a case study in the creative industry sector in Medan City. This research is quantitative, employing multiple regression analysis methods with SPSS analysis tools. The respondents in this study consists of the professionals within the creative industry sector in Medan City. The technique used for determining the participants in this investigation is a non-probability sampling approach involving incidental testing. The unknown population is estimated using the Slovin formula, resulting in an assesment numbering seventy individuals. The data collecting method in this investigation is by distributing survei forms. The results of the study show that influencer marketing and digital marketing has a good and significant impact on the popularity of brands. Influencer and digital marketing have a simultaneous impact on the popularity of brands in MSMEs: a case study in the creative industry sector in Medan City.